Humanity in the World of Life - Zhang, Hwe Ik (Zygon, 1989)
Abstract. The position and role of humanity in the world of life is examined in the light of the ontological structure of life itself. This problem is approached by considering the possible units of life representing various modes of life phenomena. I argue that the only meaningful unit of life without interposing some special external conditions is “global life” framed in a star-planet system. Any other possible unit of life exhibited by various kinds of individuals is conditional in the sense that it would leave out an essential part as “co-life.” The relationship between human being and the global life should be understood in this general scheme of individual and global life. It is emphasized, however, that human being occupies a unique position in global life in the sense that humanity can promote either a cancerous situation or a healthy higher-order enhancement of the global life.